Objectively measured physical activity levels and sedentary time in 7-9-year-old Estonian schoolchildren: independent associations with body composition parameters - Eva-Maria Riso; Merike Kull; Kerli Mooses; Aave Hannus; Jaak Jürimäe (BMC, 2016)
Abstract Background Sufficient daily physical activity (PA) is necessary for physical, social and mental health benefits during growth. Most of the available data on children is based on subjective reports, while only limited data on objective PA and sedentary levels is available for primary school children. Increased PA is also an important health indicator of body composition parameters, especially body adiposity indices. The aim of the present study was to determine objectively the amount of daily PA levels at different intensities and sedentary time in normal-weight (NW) and overweight (OW) 7-9-year-old boys and girls, and to find associations between objectively measured PA levels and sedentary time with different body composition values. Methods Two hundred and seventy eight (142 boys and 136 girls) primary school children aged 7.9 ± 0.7 years participated in this study. Objective PA intensity and sedentary levels were measured over 7 days by accelerometry. Indices of total fat mass (body fat %, sum of skinfolds), fat distribution (waist-to-height ratio) and muscular component (fat free mass [FFM]) were calculated from measured anthropometric parameters. Results There were no differences (p > 0.05) in PA intensity levels and sedentary time between boys and girls as well as between NW and OW children. About 11 % of children met the current guidelines of at least 60 min per day of moderate-to-vigorous PA (MVPA). Sedentary time was positively and negatively associated (p < 0.05) with all body fat and FFM values, respectively. Moderate and vigorous PA along with MVPA were negatively and positively associated (p < 0.05) with all body fat and FFM indices, respectively. Conclusions The results of present study showed that about 11 % of primary school children were engaged in PA of at least 60 min of MVPA daily. While MVPA is negatively associated with fat mass indices and positively associated with FFM regardless of different confounders, sedentary time is negatively related to FFM and positively with fat mass values after adjusting for several confounders. These results suggest that higher MVPA level and lower sedentary time level are important in maintaining and developing healthy body composition in primary school children during growth.